The antiviral potency of Fagus sylvatica 4OMe-glucuronoxylan sulfates - Pujol, Carlos Alberto (2016)
Herpes simplex virus belongs to Herpesviridae family and causes infection of humans from ancient times. 4OMe-glucuronoxylans as the renewable biopolymers can be promising glycomaterials for various applications in pharmacy. Control enzymatic degradation of the native 4OMe-glucuronoxylan (GX1) followed by targeted sulfation procedure afforded a range of 4OMe-glucuronoxylan sulfates differed in the degree of sulfation (10-16%) and molecular mass (21,000-5000 g/mol; GXS1 > GXS2 > GXS3 > GXS4). Antiviral activity tests on GXS1-4 against herpes simplex virus (HSV) types 1 and 2 revealed the positive effect of all compounds against strains of herpes virus. Of them, the compounds GXS1 and GXS4 were shown to be the most active for both HSV serotypes. The antiviral activity of GXS1 and GXS4 was similar to those of heparin or dextran sulfate, used as reference compounds. It was found that GXS1 and GXS4 were active as well against Polio and dengue viruses, however, on a smaller scale. The mode of antiviral action of 4OMe-glucuronoxylan sulfates is due to inhibition of the virus binding to the cell receptors.